The utility of cytokeratins 7 and 20 (CK7/20) immunohistochemistry in the distinction of short-segment Barrett esophagus from gastric intestinal metaplasia: Is it reliable? - (:unkn) unknown (My University, 2003)
BACKGROUND: The purpose of the present correlative immunohistochemical study was to assess the utility of cytokeratin (CK7 and CK20) expression in the diagnosis of short-segment Barrett esophagus, particularly its efficacy in differentiating Barrett mucosa from intestinal metaplasia of the gastric cardia and corpus. METHODS: Two groups of endoscopic biopsy specimens were examined, including 20 endoscopic biopsy specimens of short-segment Barrett esophagus (Group A) and equal number exhibiting Helicobacter pylori associated intestinal metaplasia of the gastric cardia and corpus (Group B). All were investigated by immunohistochemistry using the standard ABC method for CK7 and CK20 expression. Fisher's exact test was used for statistical analysis of Barrett CK7/20 and gastric CK7/20 patterns between the groups. RESULTS: The anticipated pattern of reactivity in Barrett mucosa (CK7: strong diffuse positivity in superficial and deep glands; CK20: positivity in surface epithelium and superficial glands) was seen in 2 cases of Group A specimens. The expected gastric pattern (CK7: patchy immunostaining with variable involvement of deep glands; CK20: patchy immunostaining of superficial and deep glands in incomplete intestinal metaplasia / absence of CK7 immunoreactivity with strong CK20 staining in superficial and deep glands in complete intestinal metaplasia) was seen in 8 cases of Group B specimens. The respective sensitivity and false-negativity values of CK7/20 staining for Barrett pattern in Group A were 10% and 90%, respectively. These values for gastric pattern in Group B were 40% and 60%, respectively. The specificity and false-positivity values of both patterns were same (100% and 0%, respectively). There was no statistically significant difference for Barrett pattern between the two groups (P = 0.487), while the observation of gastric pattern was significantly higher in Group B than in Group A (P = 0.02). CONCLUSIONS: We concluded that these hypothesized and recently applied diagnostic criteria involving CK7 and CK20 immunoreactivity are not reliable in distinguishing short-segment Barrett esophagus from intestinal metaplasia as seen in gastric cardia and corpus.